Short-term outcomes of bronchoplastic lobectomies performed from video-assisted thoracoscopic and thoracotomic approaches - M. A. Atyukov; I. Yu. Zemtsova; A. S. Petrov; O. A. Zhgemchugova-Zelenova; O. V. Novikova; S. A. Mischeryakov; P. K. Yablonskii (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of this study was to evaluate the short-term outcomes of bronchoplastic lobectomies performed from video-assisted thoracoscopic (VATS) and thoracotomic approaches and to identify factors affecting the course of the early postoperative period.METHODS AND MATERIALS. Out of 398 patients underwent surgical resection in the Center for Intensive Pulmonology and Thoracic Surgery of the SPbSBHI «City multidisciplinary hospital № 2» from 2014 to 2021 for malignant lung neoplasms, 27 patients with bronchoplastic lobectomy were included in the retrospective study. Patients were divided into two groups depending on surgical approach: group I (n=17) included patients operated via thoracotomic approach; group II (n=10) included patients who underwent VATS surgeries. The groups were similar in gender, age, smoking history, Body Mass Index, concomitant pathology, functional status and stage of the disease. Surgical intervention included ipsilateral systematic lymph dissection and bronchoplastic lobectomy.RESULTS. There were no significant differences in time of operation, blood loss, duration of drainage of the pleural cavity, incidence of postoperative complications, length of hospital stay, number of dissected lymph nodes between the groups. Factor analysis of the influence of pre- and intraoperative factors on the development of postoperative complications showed that the risk of a complicated course of the postoperative period significantly decreased at normal values of FEV1 and FVC (OR=0.942, p<0.05; OR=0.932, p><0.05) and increased in the presence of adhesions (obliteration of the pleural cavity more than 50%), requiring total pneumolysis, and the absence of interlobar fissures (OR=5.5, p><0.05; OR=6.5, p><0.05). In multivariate analysis, strong adhesions in the pleural cavity turned out to be an independent unfavorable prognostic factor for the development of postoperative complications (OR=8.567, p><0.05). CONCLUSION. The use of VATS approach does not increase the incidence of complications after bronchoplastic lobectomies. In patients with FEV1>84.9 %)CONCLUSION. The use of VATS approach does not increase the incidence of complications after bronchoplastic lobectomies. In patients with FEV1>84.9 % and FVC>101.2 %, the risk of complications after bronchoplastic lobectomies is confirmed lower. Adhesions in pleural cavity requiring total pneumolysis is an independent unfavorable factor in the development of postoperative complications.